Effects of 18-week in-season heavy-resistance and power training on throwing velocity, strength, jumping, and maximal sprint swim performance of elite male water polo players - Ramos Veliz, R.; Requena, B.; Suarez-Arrones, L.; Newton, R. U.; Saez de Villarreal, E. (The Journal of Strength and Conditioning Research, 2014)
We examined the effects of 18 weeks of strength and high-intensity training on key sport performance measures of elite male water polo (WP) players. Twenty-seven players were randomly assigned to 2 groups, control (in-water training only) and strength group, (strength training sessions [twice per week] + in-water training). In-water training was conducted 5 d/wk. Twenty-meter maximal sprint swim, maximal dynamic strength 1-repetition maximum (1RM) for upper bench press (BP) and lower full squat (FS) body, countermovement jump (CMJ), and throwing velocity were measured before and after the training. The training program included upper and lower body strength and high-intensity exercises (BP, FS, military press, pull-ups, CMJ loaded, and abs). Baseline-training results showed no significant differences between the groups in any of the variables tested. No improvement was found in the control group; however, meaningful improvement was found in all variables in the experimental group: CMJ (2.38 cm, 6.9%, effect size [ES] = 0.48), BP (9.06 kg, 10.53%, ES = 0.66), FS (11.06 kg, 14.21%, ES = 0.67), throwing velocity (1.76 km/h, 2.76%, ES = 0.25), and 20-m maximal sprint swim (-0.26 seconds, 2.25%, ES = 0.29). Specific strength and high-intensity training in male WP players for 18 weeks produced a positive effect on performance qualities highly specific to WP. Therefore, we propose modifications to the current training methodology for WP players to include strength and high-intensity training for athlete preparation in this sport.